Among the Garifuna : family tales and ethnography from the Caribbean coast - Wells, Marilyn McKillop (University Alabama Press, 2015)
"Among the Garifuna is the first ethnographic narrative of a Garifuna family. The Garifuna are descendants of the "Black Carib," whom the British deposited on Roatan Island in 1797 and who settled along the Caribbean coast from Belize City to Nicaragua. In 1980, medical anthropologist Marilyn McKillop Wells found herself embarking on an "improbable journey" when she was invited to the area to do fieldwork with the added challenge of revealing the "real" Garifuna. Upon her arrival on the island, Wells was warmly embraced by a local family, the Diegos, and set to work recording life events and indigenous perspectives on polygyny, Afro-indigenous identity, ancestor-worshiping religion, and more. The result, as represented in Among the Garifuna, is a lovingly intimate, earthy, human drama. The family narrative is organized chronologically. Part I, "The Old Ways," consists of vignettes that introduce the family backstory with dialogue as imagined by Wells based on the family history she was told. We meet the family progenitors, Margaret and Cervantes Diego, during their courtship, experience Margaret's pain as Cervantes takes a second wife, witness the death of Cervantes and ensuing mourning rituals, follow the return of Margaret and the children to their previous home in British Honduras, and observe the emergence of the children's personalities. In Part II, "Living There," Wells continues the story when she arrives in Belize and meets the Diego children, including the major protagonist, Tas. In Tas's household Wells learns about foods and manners and watches family squabbles and reconciliations. In these mini-stories, Wells interweaves cultural information on the Garifuna people with first-person narrative and transcription of their words, assembling these into an enthralling slice of life. Part III, "The Ancestor Party," takes the reader through a fascinating postmortem ritual that is enacted to facilitate the journey of the spirits of the honored ancestors to the supreme supernatural. Among the Garifuna contributes to the literary genres of narrative anthropology and feminist ethnography in the tradition of Zora Neal Hurston and other women writing culture in a personal way. Wells's portrait of this Garifuna family will be of interest to anthropologists, Caribbeanists, Latin Americanists, students, and general readers alike. "--